Do labor market programs affect labor force participation? - Kerstin Johansson (Institute for Labour Market Policy Evaluation (IFAU), 2002)
This paper estimates the macroeconomic effect of labor market programs on labor force participation. Labor market programs could counteract businesscycle variation in the participation rate that is due to the discouraged-worker effect, and they could prevent labor force outflow. An equation that determines the participation rate is estimated using panel data (1986-1998) for Swedens municipalities. The results indicate that labor market programs have relatively large and positive effects on labor force participation. If the number of participants in labor market programs increases temporarily by 100, the labor force increases by around 63 persons. The effect is temporary so the number of participants in the labor force returns to the old level in the next period. If the number of participants in programs is permanently increased, the labor force increases by around 70 persons. The results indicate that programs prevent labor force outflow because participants who would have left the labor force in the absence of programs are now participating because of the programs. Income and vacancies have positive long- and short-run effects on participation rate. Open unemployment, job destruction rate, and proportion of persons be-tween ages 18-24 and 55-65 have negative long-run effects on the participation rate.
Keywords: E64; J22; J68; 330; labor supply; labor market programs; dynamic panel data